The Normal School of Peçanha: installation, operation and organization at the beginning of the 20th century - Medeiros Carvalho, Cleonice; Talita Da Silva, Josana; Fernandes da Silva, José; Paulo Azevedo Oliveira, Davidson (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This article aims to investigate the process of installation, operation and organization of the Normal School of Peçanha, between 1914 and 1930, The school is located in the eastern region of the state of Minas Gerais – Brazil. Originality/contribution: This study makes a contribution to the field by analyzing an important institution for the social and intellectual development of the region. Method: With the purpose of conducting an in-depth research, the study focused on the analysis of the Normal Education in this institution through historical and documentary sources. The work was organized in four methodological stages: heuristic, doxography, etiology and synthesis. Information strategy/data collection: direct sources were used, such as: congregation minutes, school inspection minutes, the regulations for the creation of the Normal School of Peçanha and other regulations, laws, decrees and resolutions of higher instances, as well as indirect sources, namely: historiographic studies of normal schools in Brazil and in the regional context. Conclusions: the research shows that the creation and organization of this institution was a political act by the local elite that resulted in the institutionalization of teacher formation for primary education.